2013
DOI: 10.1159/000345105
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, Safety and Tolerability of an Optimized Avulsion Technique with Onyster® (40% Urea Ointment with Plastic Dressing) Ointment Compared to Bifonazole-Urea Ointment for Removal of the Clinically Infected Nail in Toenail Onychomycosis: a Randomized Evaluator-Blinded Controlled Study

Abstract: Background: Toenail onychomycosis is highly prevalent, with 14-28% of people aged 60 or over suffering from the disease. Use of a topical antifungal alone in toenail onychomycosis is associated with low cure rates. This may be due to limited penetration of the topical antifungal through the diseased nail. The objective of the present study was to compare two treatment modalities to obtain diseased nail chemical avulsion in toenail onychomycosis. Methods: In this European, multicenter, randomized, parallel-grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 21 publications
(31 reference statements)
0
31
0
1
Order By: Relevance
“…Debridement alone was shown to be ineffective in achieving mycological cure [27] . As shown recently by our group in a randomized clinical trial, an optimized avulsion technique associated with topical antifungal treatment is associated with a high cure rate of dermatophytic onychomycosis [22] . Debridement, when used as an adjunct therapy, improved treatment satisfaction and reduced symptom frequency [28] .…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Debridement alone was shown to be ineffective in achieving mycological cure [27] . As shown recently by our group in a randomized clinical trial, an optimized avulsion technique associated with topical antifungal treatment is associated with a high cure rate of dermatophytic onychomycosis [22] . Debridement, when used as an adjunct therapy, improved treatment satisfaction and reduced symptom frequency [28] .…”
Section: Discussionmentioning
confidence: 60%
“…In a recent controlled study [22] , it was shown that chemical nail avulsion using RV4104A ointment (class I medical device containing 40% urea) followed by mechanical debridement was an effective procedure to remove clinically infected nail. As a result of its composition, RV4104A ointment (with specific plastic dressing) will exert a keratinolytic effect on nail keratin.…”
mentioning
confidence: 99%
“…Although urea ointments are available OTC, the success rate of home debridement, without the support of a health professional, remains largely unexplored. Based on the available evidence, home debridement with urea ointment may be challenging, with reported failure to completely debride the affected nail area after 3 weeks ranging between 40%‐60% . A previous study on onychomycosis, comparing the efficacy of urea and bifonazole alone to that of the same local therapy combined with short‐term oral griseofulvin, showed that the mean time to detachment of the diseased nail was longer than the recommended 2‐3 weeks of treatment (24.9 days) .…”
Section: Discussionmentioning
confidence: 94%
“…The combination regimen of urea 40% ointment and bifonazole 1% cream (Canesten ® Fungal Nail Treatment Set; Bayer, Pymble, Australia) provides chemical nail ablation followed by topical antifungal treatment. Urea 40% ointment under occlusion possesses keratolytic properties and is indicated for the softening and removal of the diseased/dystrophic nails in onychomycosis . Bifonazole 1% cream is a broad‐spectrum imidazole with antifungal activity, rubbed into the nail bed after nail debridement .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation